Efectividad del Programa Educativo Nivel de Conocimiento y Practicas de Cuidado del Adulto Mayor Autovalente en cuidadores familiares - Chavez Cárdenas, Esther Noemí (2013)
This research study is quasi-experimental design and contrasting pre and posttest was performed in the Town Center of Trujillo Alto during the months of November 2012 to May 2013, in order to determine the effectiveness of educational program on the level of knowledge and care practices for older autovalente essential. The sample consisted of 25 caregivers, who were appointed at random, and that formed the experimental group. To obtain the data are used as instruments: a format of pretest and posttest of the level of knowledge and practices of family caregivers on elder care autovalente essential, consisting of 18 questions valid and reliable, considering the rights applied of anonymity, voluntary participation and confidentiality. Data processing was performed using SPSS FOR WINDOWS Version 17; the results are presented in tables of absolute and relative frequency percentage. The statistical analysis reported educational program effectiveness by analyzing the test of "Student's t" for the comparison of means for independent and paired samples to examine changes before and after the implementation of the program, with high statistical significance level. Keywords: Nursing Education Program - Family Caregivers - Elderly autovalente - Basic Care